2020
DOI: 10.1002/ajs4.145
|View full text |Cite
|
Sign up to set email alerts
|

Child protection services for children with special healthcare needs: A population record linkage study

Abstract: Children with disabilities are known to have high rates of contact with child protection services. However, little is known about child protection contacts for a broader group of children with special healthcare needs (SHCN; i.e., special needs or other impairments of concern that affect learning). This study examined the characteristics of contact with child protection services (prior to the age of 6 years) for children with SHCN identified at school entry using the 2009 Australian Early Development Census, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The current issue on Big Data and Social Policy brings together ten papers, which we have divided into three sets: one set discuss the technical challenges and institutional barriers involved in the construction and governance of linked government data assets (Gulliver, Fahmi & Abramson, 2021; Homel et al, 2021; von Sanden & Neideck, 2021); another set of papers demonstrate the application of big data to social policy issues, thereby showcasing its potential for generating valuable insights (Hindmarsh et al, 2021; Stewart et al, 2021); the final set of papers – and the accompanying commentary from Bell et al – critically interrogate the potential for big data to produce social harms.…”
Section: Ajsi Special Issue On Big Data and Social Policy In Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…The current issue on Big Data and Social Policy brings together ten papers, which we have divided into three sets: one set discuss the technical challenges and institutional barriers involved in the construction and governance of linked government data assets (Gulliver, Fahmi & Abramson, 2021; Homel et al, 2021; von Sanden & Neideck, 2021); another set of papers demonstrate the application of big data to social policy issues, thereby showcasing its potential for generating valuable insights (Hindmarsh et al, 2021; Stewart et al, 2021); the final set of papers – and the accompanying commentary from Bell et al – critically interrogate the potential for big data to produce social harms.…”
Section: Ajsi Special Issue On Big Data and Social Policy In Australiamentioning
confidence: 99%
“…Those with special healthcare needs were more likely to have a history of being exposed to neglect and physical abuse and of being placed in out‐of‐home care compared with their peers. This paper is the first Australian research to document the association between special healthcare needs and child protection, although it is well documented that children with disabilities are at greater risk of being in child protection services (Hindmarsh et al, 2021; Maclean et al, 2017). Hindmarsh et al recommend that health screening of children should occur for children reported to protection services, and their findings suggest more engagement of early intervention and health services are required prior to school.…”
Section: Ajsi Special Issue On Big Data and Social Policy In Australiamentioning
confidence: 99%
See 1 more Smart Citation